Dental Caries in Children and Its Relationship with Parenting Styles: A Systematic Review - María Moya-López; Ana Ruiz-Guillén; Martin Romero-Maroto; María Carrillo-Díaz (MDPI AG, 2024)
Background: It can be affirmed that the parenting style of parents has an impact on the health-related behaviors of their children; the environment that parents create for their children can have an impact on both their habits and their oral health, and on the incidence of dental caries in children. The purpose of this study was to analyze the association between parenting style and childhood dental caries. Methods: Two researchers independently searched the English literature published up to May 2024 in four databases (PubMed, Web of Science, Scopus y Cochrane Library). The risk of bias was evaluated using the Modified Newcastle-Ottawa Quality Assessment Scale (NOS). This study is registered on PROSPERO (CRD42024573447). Results: Of the 130 studies identified, nine of them, with a total of 4250 participants, met our inclusion criteria. The evidence on the relationship between parenting styles and dental caries is varied. Of the studies reviewed, three showed a significant association between both factors, while four found no correlation, and two reported no significant differences in relation to parenting styles and the occurrence of dental caries. Conclusions: This discrepancy emphasizes the need for further research. Parenting styles impact child dental behavior on a global level, highlighting the relevance of recognizing these approaches in a dental context, given that parents have a fundamental role in guiding their children's behaviors.